To simplify the expression \(7^{-4} \cdot 7^{3} \div 49^{\frac{1}{2}}\), we can follow these steps:
-
Combine the powers of 7: \[ 7^{-4} \cdot 7^{3} = 7^{-4 + 3} = 7^{-1} \]
-
Simplify \(49^{\frac{1}{2}}\): Since \(49 = 7^2\), we have: \[ 49^{\frac{1}{2}} = (7^2)^{\frac{1}{2}} = 7^{2 \cdot \frac{1}{2}} = 7^{1} = 7 \]
-
Now we can write the expression as: \[ 7^{-1} \div 7 = 7^{-1} \cdot 7^{-1} = 7^{-1 - 1} = 7^{-2} \]
-
Convert back from negative exponent: \[ 7^{-2} = \frac{1}{7^2} = \frac{1}{49} \]
The simplified expression is: \[ \frac{1}{49} \]